Comparative assessment on climate prediction from CMIP5 and CMIP6 models over Hulu Terengganu, Malaysia - Wan Amirul Syahmi, Wan Mazlan; Nurul Nadrah Aqilah, Tukimat (IOP Publishing Ltd., 2023)
The uncertainties of climate change in the future year cause the contribution factors and greenhouse gasses (GHGs) effects on the local climates need to be revised. The development of new climate scenarios in the 6th Coupled Model Intercomparison Project (CMIP6) is consistent with the technological exploration and increment of GHGs dispersion compared to the consideration factors in CMIP5. The purpose of this study was to compare the performance of CMIP5 (based on Representative Concentration Pathways, RCPs) and CMIP6 (based on Shared Socioeconomic Pathways, SSPs) in simulating seasonal rainfall and estimating trends in Hulu Terengganu, Malaysia. The linear scaling (LS) method was used in this study to treat the gaps between observed and simulated results, and the climate trend was examined using the Mann-Kendall (MK) and Sen's Slope tests. The results show that the SSPs scenario outperforms the RCPs in simulating historical rainfall (2015-2020) by producing a higher r value and a smaller percentage difference. According to the MK test, there was no significant trend in projected rainfall across all scenarios (2020-2099). Based on Sen's Slope test, RCP 4.5 and RCP 8.5 show an increasing trend for all rainfall stations. However, all SSP scenarios show a declining trend in projected rainfall, with SSP1-2.6 producing the largest declining trend magnitude. In contrast, when compared to observed rainfall from the baseline period (1988-2017), the SSPs scenario indicates the potential for a greater increase in future annual rainfall projections than the RCPs scenario. All SSP scenarios show an increasing annual rainfall magnitude in 2040-2069 (Δ2050). However, the annual rainfall for SSP2-4.5 and SSP5-8.5 began to decrease in 2070-2099 (Δ2080). Meanwhile, RCP 2.6 has the greatest reduction in annual rainfall projections for both projected time periods when compared to other scenarios. It can be concluded that although all SSPs scenarios show a declining trend in projected rainfall from 2020 to 2099, the total annual rainfall projected for SSPs remains higher than RCPs in Δ2050 and Δ2080 periods.